A Single Institution's Experience of Primary Headache in Children With Celiac Disease. (January 2020) - Hom, Grant L.; Hom, Brian L.; Kaplan, Barbara; Rothner, A. David
Background: Few studies exist examining the frequency of primary headache in children with celiac disease and the impact of a gluten-free diet on primary headache symptomology. This study explores characteristics and frequency of headaches in children with celiac disease and response to gluten-free diet at a single institution. Methods: Medical records were reviewed for children with celiac disease confirmed by the presence of elevated tissue transglutaminase IgA levels and histologic changes consistent with the diagnosis of celiac disease on small bowel biopsy. Eligible participants were contacted via letter for participation in a phone survey regarding headaches. Phone interviews were conducted 2 weeks after notification and lasted approximately 10 minutes. Headaches were classified according to ICHD-3 criteria. Results: 247 eligible patients or their families were contacted. A total of 132 (53.44%) agreed to participate. One participant was excluded due to insufficient information provided. Overall, 51 of 131 participants had recurrent headache defined as at least 1 episode per month (39%, 95% confidence interval [CI]: 31%-47%) and 33 had migraine with or without aura (25%, 95% CI: 18%-33%). Twenty-eight had frequent tension-type headache (22%, 95% CI: 15%-29%). Thirty-two participants noted headaches before a confirmed diagnosis of celiac disease. Twenty-two of 32 participants (68.75%) noticed decreased headache frequency or intensity, or both, after starting the gluten-free diet. Conclusion: This study suggests that at least one-third of children and adolescents with celiac disease have recurrent headaches at the time of diagnosis. A gluten-free diet led to improved headache symptomology in a significant number of these patients.